2014
DOI: 10.1128/aac.02922-14
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial Comparing 7-Day Triple, 10-Day Sequential, and 7-Day Concomitant Therapies for Helicobacter pylori Infection

Abstract: e With the rising prevalence of antimicrobial resistance, the failure rate of the standard triple therapy for Helicobacter pylori infection is increasing. Sequential therapy and concomitant therapy have been recommended to replace standard triple therapy for H. pylori eradication in regions with high clarithromycin resistance. The aim of this prospective, randomized, and controlled study was to simultaneously assess the efficacies of 10-day sequential and 7-day concomitant therapies versus a 7-day standard tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 38 publications
2
74
3
Order By: Relevance
“…There was no difference in the effect of CT in clarithromycin-sensitive and resistant groups [38] as well as in metronidazole-sensitive and resistant groups [39]. Several studies showed that there was no difference in the effectiveness of CT and ST in clarithromycin and metronidazole-sensitive or resistant groups [40,41]. Moreover, this study showed that eradication rates of these two therapies were similar, too.…”
Section: Discussionmentioning
confidence: 59%
“…There was no difference in the effect of CT in clarithromycin-sensitive and resistant groups [38] as well as in metronidazole-sensitive and resistant groups [39]. Several studies showed that there was no difference in the effectiveness of CT and ST in clarithromycin and metronidazole-sensitive or resistant groups [40,41]. Moreover, this study showed that eradication rates of these two therapies were similar, too.…”
Section: Discussionmentioning
confidence: 59%
“…The data provided by Georgopoulos et al can be compared to those published in previous studies [25][26][27][28], in which the relative efficacy of concomitant regimen was consistently and significantly superior to that of sequential therapy throughout all the resistance profiles. If we pool previous data, concomitant offers a 15% benefit (risk difference) in clarithromycin-resistant patients, a 14% in the case of metronidazole resistance and, finally, a 38% in dual resistance.…”
Section: Editorialmentioning
confidence: 88%
“…In a multicenter prospective RCT conducted in a high clarithromycin resistant area, concomitant therapy (esomeprazole, 40 mg; amoxicillin, 1 mg; clarithromycin, 500 mg; metronidazole, 500 mg bid*10d) had significantly higher eradication rates of 89% and 93.4% (versus 78.7%/82.8% of sequential therapy) according to ITT and PP analyses, respectively, despite drug resistances (metronidazole, 34%; clarithromycin, 27%; and dual drugs ,7.9%) on culture [9]. In another study, 7 days of concomitant therapy (pantoprazole, 40 mg; amoxicillin, 1 mg; clarithromycin, 500 mg; metronidazole, 500 mg bid) showed eradication rates of 94.1%, which was significantly higher compared to that of 7-day standard triple therapy (81.6%) and 10-day sequential therapy (89.2%) [65]. Additionally, 7-day concomitant therapy (Rebeprazole, amoxicillin, clarithromycin, metronidazole) showed eradication rates of 90.3% [57].…”
Section: Concomitant Therapymentioning
confidence: 96%
“…In another study with omeprazole, 20 mg; amoxicillin, 1 gm; clarithromycin, 500 mg; and tinidazole, 500 mg for 14 day, the eradication rates were 86.3% and 95% according to ITT and PP analyses, respectively [60], whereas the 5-day treatment showed eradication rates of 85.5% and 91.6% according to ITT and PP analyses, respectively [62]. Therefore, these therapies with 7-14 day durations can be an alternative to sequential therapy in high drug resistance areas and also in settings where bismuth is not available [9,57,62,65,66].…”
Section: Concomitant Therapymentioning
confidence: 99%